Differences in Regional Development in the Northern Great Plain Region - Harsányi, Endre; Harsányi, Gergely; Nagy, János Attila (Acta Agraria Debreceniensis, 2005)
An important ambition of EU regional politics is the reduction of disparities. An important strategical objective of the Commission is to terminate underdevelopment and to ensure the development of the regions based on the principles of solidarity, equity and justice. The commission has dedicated forty percent of its common budget to achieve these goals. The differences in development are significantly influenced by the economic characteristics of the specific region, the quality and quantity of human resources, the accessibility of the region and factors influencing local quality of life.The new spatial structure has been formed by the processes of the change of regime, the events of nineties and the economic renewal based onforeign capital investments parallel with crisis phenomenon. The economic, political and social consequences of the transformation have significantly transformed spatial structure and increased disparities. New disparities have formed, which strengthened due to the formation of east-west slopes and local crisis zones. The outstanding improvement of the capital resulted in great regional development differences, which can be detected when examining regional distribution of gross domestic product. The Eastern part of the country was most heavily affected by the collapse of heavy industry and agricultural mass production based on the Eastern markets.It is of key importance for the region to strengthen regional competitiveness, which requires the application of consistent development-politics. Economic development is the most important, which can also draw the possibility of establishing welfare infrastructures. It is important to develop the processing industry, the supply networks and to ease the lack of capital it is also important to involve foreign capital. Developing agriculture plays an important role in transforming the structure of the economy. Since the conditions of the region, its traditions and long-term competitive advantages are favorable, thus can represent a greater ratio in the economy than the EU average. The modernisation of the agricultural sector can be promoted by supporting marketing, quality agricultural development and producer-retail cooperation. It is also highly important to promote development in transportation and informatics infrastructure and human resources.In the future – based on the strength of the region – it is necessary to achieve such a consistent regional development politics, which by validating the principles of regional politics, serves the interest of utilizing regional development supports most efficiently and prevents the irreversible underdevelopment of the region and promotes fast development.